2021
DOI: 10.3390/nu13062114
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Behaviors and Incident COVID-19 in the UK Biobank

Abstract: Background: Nutritional status influences immunity but its specific association with susceptibility to COVID-19 remains unclear. We examined the association of specific dietary data and incident COVID-19 in the UK Biobank (UKB). Methods: We considered UKB participants in England with self-reported baseline (2006–2010) data and linked them to Public Health England COVID-19 test results—performed on samples from combined nose/throat swabs, using real time polymerase chain reaction (RT-PCR)—between March and Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 64 publications
5
33
3
Order By: Relevance
“…Fruit and vegetables indeed provide a mix of these highly relevant compounds for the immune function (as discussed above), and also other bioactive compounds such as polyphenols [ 43 ]. Our findings regarding the consumption of vegetables are consistent with those of the recently published prospective study in the UK-Biobank [ 5 ]. A retrospective study in pregnant women also suggested a moderate effect of fruit and vegetable intake in the prevention of URTI [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Fruit and vegetables indeed provide a mix of these highly relevant compounds for the immune function (as discussed above), and also other bioactive compounds such as polyphenols [ 43 ]. Our findings regarding the consumption of vegetables are consistent with those of the recently published prospective study in the UK-Biobank [ 5 ]. A retrospective study in pregnant women also suggested a moderate effect of fruit and vegetable intake in the prevention of URTI [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, the outcome assessment in this study was based on self-reported questionnaires collecting SARS-CoV-2 diagnostic tests, and not seroprevalence. On the other hand, a study in the UK-Biobank reported a protective association for higher intakes of coffee and vegetables and higher odds of infection associated with higher intakes of processed meat [ 5 ]. However, this study was conducted only among participants who sought COVID-19 testing, and based on a non-detailed dietary assessment, using a simplified 17-item questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the UK Biobank, the risk of COVID‐19 positivity was lower when consuming vegetables and higher when consuming processed meats. 15 …”
Section: Implications Of the Covid‐19 Pandemic For Digestive Health And Carementioning
confidence: 99%
“…Initially micronutrients were mainly analyzed, particularly vitamins (20,21). Afterwards, the antioxidant, antiinflammatory, and antiviral activities of some nutrients and foods have been evaluated (6,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Less evidence is available for the effect of complete dietary patterns on COVID-19 (4,32,(34)(35)(36)(37)(38), and most published reports on dietary patterns are related to the changes in diet caused by the pandemic or the lockdown.…”
Section: Introductionmentioning
confidence: 99%